(untitled) - Kennedy, Terry (New York, NY., 2002)
Here is a convenient, one-of-a-kind, quick reference tool designed to provide roofing information in a flash. At last, a breakthrough for roofing professionals, architects, contractors, suppliers, or anyone in need of instant, fingertip access to information for tackling the most difficult problems effectively, economically, and fast!
Keywords: Roofing,Roofs; Handbooks, manuals, etc.,Design and construction,Handbooks, manuals, etc